Alliance rises in the West : labor, race, and solidarity in industrial California - Sunseri, Charlotte K. (Historical archaeology of the American West, 2020)
"This volume explores how pluralistic communities thrived in California's mining hinterland as well as how immigrants and California Natives mobilized or mitigated power inequalities through their daily experiences of identity expression, community cohesion, and labor relations"--